2007
DOI: 10.1128/aem.00565-07
|View full text |Cite
|
Sign up to set email alerts
|

DegU and YczE Positively Regulate the Synthesis of Bacillomycin D byBacillus amyloliquefaciensStrain FZB42

Abstract: Environmental strain Bacillus amyloliquefaciens FZB42 differs from the domesticated model organism of the same genus, Bacillus subtilis 168, in its ability to promote plant growth and suppress plant-pathogenic organisms present in the rhizosphere. This behavior is exerted mainly through the production of several nonribosomal cyclic lipopeptides and polyketides, which exhibit a broad range of action against phytopathogenic bacteria, fungi, and nematodes. Here, we provide evidence that the synthesis of the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 48 publications
3
78
0
Order By: Relevance
“…In this transposon mutant, pMarA was integrated into the degU gene, which is a global transcriptional regulator that activates the bacillomycin D promoter (20). Coincidentally, we observed by high-performance liquid chromatography (HPLC)-electrospray ionization mass spectrometry (ESI-MS) that PZN is overproduced by this strain (see Fig.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…In this transposon mutant, pMarA was integrated into the degU gene, which is a global transcriptional regulator that activates the bacillomycin D promoter (20). Coincidentally, we observed by high-performance liquid chromatography (HPLC)-electrospray ionization mass spectrometry (ESI-MS) that PZN is overproduced by this strain (see Fig.…”
Section: Methodsmentioning
confidence: 82%
“…The nonconcentrated, cell surface extract of RSpMarA2, the strain which bears a mariner transposon insertion in the degU global transcriptional regulator gene (20), contains significantly higher levels of cpd1335 than those in the wild type and the RS6 mutant strain (Table 1; Fig. 3A).…”
Section: Maldi-tof Ms Detection Of a New Metabolite From Fzb42 With [mentioning
confidence: 99%
“…Sequencing of the region next to the transposon insertion revealed that in mutant WY01, the RBAM_029230 gene was interrupted by the transposon insertion, while mutant RSpMarA2 harbored an interrupted degU gene, suggesting that synthesis of the antibacterial compound is strictly dependent on DegU. DegU, a global transcription regulator, activates the nonribosomal synthesis of the polyketide difficidin, the antifungal lipopeptide bacillomycin D, and bacilysin in FZB42 (23,24).…”
Section: Detection Of a Gene Cluster Involved In Bacteriocin Biosynthmentioning
confidence: 99%
“…One such example is the Bacillus subtilis DegS-DegU pair, which controls various cellular processes. These include competence development (6,10,11,25), swarming, flagellum formation (1,16), biofilm formation (15,35), osmotic response (29), poly-␥-glutamic acid synthesis (35), salt resistance (19), antibiotic synthesis (17), and the synthesis of extracellular degradative enzymes (21). It has been proposed that some of the events regulated by the DegS-DegU system are manifested by different extents of phosphorylation of the response regulator DegU by the DegS kinase (16,40).…”
mentioning
confidence: 99%